2013
DOI: 10.2220/biomedres.34.41
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a stable T lymphoma cell line transduced with HLA-A^|^lowast;24:02-restricted WT1-specific TCR genes and its application to antigen-specific immunomonitoring

Abstract: Wilms' tumor gene 1 (WT1) has been proposed as an attractive target for cancer immunotherapy. A natural 9-mer peptide (CYTWNQMNL), which bound to human leukocyte antigen (HLA)-A*24:02, was identified from among WT1-specific cytotoxic T lymphocyte (CTL) epitopes. This natural WT1 CTL epitope peptide was further modified (CMTWNQMNL) to enhance its binding affinity to HLA-A*24:02. This modified WT1 CTL epitope peptide was superior to the natural peptide for inducing HLA-A*24:02-restricted WT1-specific CTLs. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The reason that different TCR clone amplification induced by the same peptide, is due to the individual T cell response from different donors and patients. There were also studies showing different TCR clone ( TCR Vβ 5-1- Dβ 2- Jβ 2-5) inducted by WT1 (CMTWNQMNL) peptides [44]. Overall, the new identified TCR V β 11-2- Dβ 1- Jβ 1-1 clone in this study may provide new data of WT1 specific TCR clone bank.…”
Section: Discussionsupporting
confidence: 55%
“…The reason that different TCR clone amplification induced by the same peptide, is due to the individual T cell response from different donors and patients. There were also studies showing different TCR clone ( TCR Vβ 5-1- Dβ 2- Jβ 2-5) inducted by WT1 (CMTWNQMNL) peptides [44]. Overall, the new identified TCR V β 11-2- Dβ 1- Jβ 1-1 clone in this study may provide new data of WT1 specific TCR clone bank.…”
Section: Discussionsupporting
confidence: 55%
“…To investigate CD8 dependency of TCR‐HLA interaction, ITG‐MT3 TCR and FKS‐D11P TCR genes were transfected to J.RT3‐T3.5 cells, CD8 and TCR β chain‐deficient mutant Jurkat cells . As a result, both transduced TCR could react with specific tetramers, but the CD8‐dependent WT1 TCR could not react with the WT1 tetramer (Figure A). These results suggested that both ITG‐MT3 and FKS‐D11P TCR could react with the peptide/HLA complex in a CD8‐independent way.…”
Section: Resultsmentioning
confidence: 99%
“…Affinity of FKS-D11P TCR (K D value of 4.70 × 10 −9 mol/L) was much higher than that of naturally occurring TCR binding to HLA class I/peptides (K D value of 1-50 × 10 −6 mol/L). 21 In previous studies on a soluble TCR-multimer, K D values of TCR for HLA-A2/HTLV type 1 Tax [11][12][13][14][15][16][17][18][19] , HLA-A2/HBV env [183][184][185][186][187][188][189][190][191] , HLA-A2/MART1 26-35(A27L) and HL A-A2/NY-ESO-1 157-167(C165V) were 1.06 × 10 −6 , 0.6 × 10 −6 , 5.4 × 10 −6 and 4.3 × 10 −6 mol/L, respectively. 17,19,20 These results suggested that the affinities of successfully constructed soluble TCR were also higher than the general affinity of TCR.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations